Flywheel resistance training for change of direction performance: A systematic review - Michalak, M. M.; Ryan, C. M.; Ehlert, A.; Cronin, J. (Strength and Conditioning Journal, 2026)
Flywheel resistance training (FRT) is increasingly applied to enhance athletic performance, particularly for change of direction (COD) tasks. Although researchers have reported reductions in COD time after FRT, uncertainty remains regarding how FRT has been implemented and how reported outcomes vary across populations, loading strategies, and task demands. The objective of this article was to systematically review and descriptively synthesize the literature examining the effects of FRT on COD performance. A secondary aim was to contextualize reported COD outcomes after FRT relative to other resistance training modalities, where comparisons were available. This review followed PRISMA guidelines. Four databases (PubMed, Google Scholar, ScienceDirect, SPORTDiscus) were searched. Risk of bias was assessed using the Cochrane RoB 2 tool. FRT interventions were generally associated with reductions in COD test times across a range of COD approach angles, athlete populations, and sporting contexts. Reductions in COD time were most common when FRT was implemented once weekly using low-to-moderate inertial loads (0.005-0.05 kg·m2), particularly when exercises emphasized lateral movements. Larger relative reductions in COD time occurred in tasks involving directional changes =90° and in elite athletes. Comparisons with traditional resistance and plyometric training yielded mixed findings, with several studies reporting changes in COD time across modalities. FRT seems to be a viable training stimulus for improving COD performance; however, heterogeneity in protocols, outcome, and risk-of-bias profiles limits definitive conclusions regarding optimal parameters or modality superiority. Findings should therefore be interpreted as descriptive and hypothesis-generating.